Increasing English Translation Skill through Grammar Translation Method at the Fifth Semester Students of English Education Program at STKIP Kie Raha Ternate - Sahrun Sudirman (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2021)
This study aims to describe the improvement of translation skills through a combination of the grammar translation method. This study shows that the students' translation skills have not improved significantly. This can be seen from the achievement of student understanding. The results obtained through a questionnaire show that the translation course is very liked by 66.7 percent of students. Meanwhile, other aspects have not been seen to increase optimally. For assignments / exercises the percentage of 53.3 percent of students showed sufficient results. Meanwhile, for the implications and benefits aspects, the achievement was only in the range of 13.3 percent and the benefits aspect of 20.0 percent.